Configuring center-periphery relations: relational legacy in the over-centralized state - Trubina, Elena (Journal of Architecture and Urbanism, 2015)
This essay explores the idea of relational legacy in connection to the interconnected group of central and provincial cities. The concept is applied to concrete explorations of the relationship between the cities. We explore the idea through the emergence of discourses on nation, interurban differences and various conceptions of belonging. We find that the relational dynamics of urban space has been actively constructed by the media. It is concluded that existing conceptions of interurban relations need to take account of the contradictory dynamics behind the urbanites’ perception of cities. We also need to contend with manifestations of “state racism” which appear to achieve a greater prominence.